A Phenomenological Analysis of the Anointing among Religious Serpent Handlers - Williamson, W. Paul (The international journal for the psychology of religion, 2000)
Holiness-Pentecostal sects that practice serpent handling do so out of compliance with a literal interpretation of Mark 16:17-18. To investigate the meaning of this practice from within its religious context, phenomenological interviews were conducted with 8 men and 3 women who focused on specific experiences of taking up serpents. Participants reported that serpents were taken up either by faith or by the anointing, but most often by the anointing. From transcripts of these interviews, descriptions of the anointing were presented to an interpretive research group for thematic analysis using hermeneutic techniques. This analysis revealed that the anointing was described as an embodied experience involving an awareness of five themes: (a) "God moving on me," (b) a feeling of empowerment, (c) "indescribable" good feelings, (c) a sense of feeling "not there" in the immediate context, and (d) a "contagious flow." Relationships among these themes and the existential grounds of body, time, others, and world are discussed, as well as the significance of this type of study for other methodological investigations of the anointing experienced by members of Holiness-Pentecostal sects.